The theory of plasma heating and confinement in a multislit electromagnetic trap - Lavrent’ev, O.A. (Вопросы атомной науки и техники, 2003)
In the article the circle of questions connected to plasma heating and confinement in a multislit electromagnetic trap with axisymmetric geometry of a magnetic field is considered: plasma formation and heated by electrons injection, electrons cross transfer in a space of coordinates and in a space of speeds, ions losses through ring magnetic slits and axial holes, recuperation and direct transformation of a - particles kinetic energy in electrical one. The accounts of the basic characteristics thermonuclear reactor “Elemag” are offered.